WPSIII-1 Ultrastructure and elementary composition of the eggshell according to hen age. - Sohn, S (J Anim Sci, 2018)
An eggshell is a complex and highly ordered structure which composed of several mineralized layers. The quality of eggshell is very important factor for food safety and marketing. It is well known that the eggshell quality decreases with increasing hen age. This study was to investigate the changes of eggshell structure and shell composition according to hen age. In the microscopic observations of the uterus endometrium, histological deformation, fibrosis, atrophy and elimination of micro-villi were found with increasing hen age. The concentration of blood-ion components such as Ca(2+), Na(+), K(+), and Cl(-) ions did not change with age. As the results from ultrastructure analysis of eggshell, the palisade layer ratio and the density of mammillary knobs significantly decreased with increasing hen age. In addition, a number of type B mammillary knobs were observed in shell with increasing hen age. In the mineral element assay from eggshell, Ca(2+), S(2-) and Co(2+) significantly decreased with increasing hen age, whereas Na(+), K(+) and V(2+) significantly increased. Decreasing mammillary knob density and palisade layer ratio causes cracking of the egg shell and facilitates bacterial invasion. The high incidence of type B mammillary knobs, which are a type of broken crystal debris, weaken the egg shell and cause to easily egg break. Decreasing the major transport ions such as Ca(2+), S(2-) and Co(2+) causes negatively affect eggshell crystallization. Therefore, endometrial tissue damages inhibit the processes of ion transmission and crystallization for eggshell formation and causing a large and non-uniform mammillary knob formation. It means the damage of endometrial cells due to aging affects the formation of poor eggshell structure. In conclusion, aging of the hen reduces the quality of the eggshell.